Pengembangan Media Pembelajaran Scrapbook pada Materi Cerita Rakyat Bengkulu untuk Siswa Kelas IV dalam Pembelajaran Bahasa Indonesia Sekolah Dasar - Yolanda Fresiska Jaya; Puspa Djuwita; Abdul Muktadir (UNIB Press, 2023)
This study aims to describe the development of Scrapbook media products and describe the feasibility, and practicality of Bengkulu folklore-based scrapbook media. This research uses a type of research and development (R&D) that adapts the 4D model, namely Define, Design, Development, and Disseminate. For data collection, the technique used was interviewing teachers to find out the needs and responses of teachers and using a student questionnaire to find out the needs and responses of students to the Bengkulu folklore-based scrapbook media. The data obtained were analyzed using Aiken's V formula. This development research produced a product in the form of Bengkulu folklore-based scrapbook media. For the feasibility of material, language, and graphics, this scrapbook media is declared very feasible. In addition, the level of practicality of the teacher's responses and student responses is stated to be very practical.